Two phenylethanoid glycosides, Parvifloroside A and B, isolated from Barleria strigosa - Prapalert W. (2017)
© 2017, Chiang Mai University. All rights reserved. Two phenylethanoid glycosides, parvifloroside A (1) and parvifloroside B (2) have been isolated for the first time from the MeOH extract of Barleria strigosa growing in Thailand. The structures of these compounds were elucidated from their 1D and 2D NMR spectroscopic data and ESI-MS.